Importance of access to epilepsy monitoring units during the COVID‐19 pandemic: consensus statement of the International League Against Epilepsy and the International Federation of Clinical Neurophysiology. Issue 4 (17th August 2021) - Beniczky, Sándor; Husain, Aatif; Ikeda, Akio; Alabri, Haifa; Cross, J. Helen; Wilmshurst, Jo; Seeck, Margitta; Focke, Niels; Braga, Patricia; Wiebe, Samuel; Schuele, Stephan; Trinka, Eugen
Abstract: Restructuring of healthcare services during the COVID‐19 pandemic has led to lockdown of epilepsy monitoring units (EMUs) in many hospitals. The ad‐hoc taskforce of the International League Against Epilepsy (ILAE) and the International Federation of Clinical Neurophysiology (IFCN) highlights the detrimental effect of postponing video‐EEG monitoring of patients with epilepsy and other paroxysmal events. The taskforce calls for action for continued functioning of EMUs during emergency situations, such as the COVID‐19 pandemic. Long‐term video‐EEG monitoring is an essential diagnostic service. Access to video‐EEG monitoring of the patients in the EMUs must be given high priority. Patients should be screened for COVID‐19, before admission, according to the local regulations. Local policies for COVID‐19 infection control should be adhered to during the video‐EEG monitoring. In cases of differential diagnosis in which reduction of antiseizure medication is not required, home video‐EEG monitoring should be considered as an alternative in selected patients.